Pilot Validation Study: Canadian Global Rating Scale for Colonoscopy Services - Stéphanie Carpentier; Nour Sharara; Alan N. Barkun; Sara El Ouali; Myriam Martel; Maida J. Sewitch (Canadian Journal of Gastroenterology and Hepatology)
Background. The United Kingdom Global Rating Scale (GRS-UK) measures unit-level quality metrics processes in digestive endoscopy. We evaluated the psychometric properties of its Canadian version (GRS-C), endorsed by the Canadian Association of Gastroenterology (CAG). Methods. Prospective data collection at three Canadian endoscopy units assessed GRS-C validity, reliability, and responsiveness to change according to responses provided by physicians, endoscopy nurses, and administrative personnel. These responses were compared to national CAG endoscopic quality guidelines and GRS-UK statements. Results. Most respondents identified the overarching theme each GRS-C item targeted, confirming face validity. Content validity was suggested as 18 out of 23 key CAG endoscopic quality indicators (78%, 95% CI: 56–93%) were addressed in the GRS-C; statements not included pertained to educational programs and competency monitoring. Concordance ranged 75–100% comparing GRS-C and GRS-UK ratings. Test-retest reliability Kappa scores ranged 0.60–0.83, while responsiveness to change scores at 6 months after intervention implementations were greater (P<0.001) in two out of three units. Conclusion. The GRS-C exhibits satisfactory metrics, supporting its use in a national quality initiative aimed at improving processes in endoscopy units. Data collection from more units and linking to actual patient outcomes are required to ensure that GRS-C implementation facilitates improved patient care.